Análise funcional como instrumento de inclusão no ensino de língua estrangeira. - Sousa, Frances Diana Tornabene de (Universidade Federal de São Carlos, 2004)
The objective of this study was to implement and evaluate the effects of a workshop for English language teachers in how to plan teaching strategies based on a functional analysis of the student s performance. An underlying supposition was that teaching centered on student needs could result in academic and social inclusion for students as a by product of learning achievement. The workshop was taught in two modules, the first to supply a conceptual base on learning differences and special educational needs and the second to supply a conceptual base and teach functional analysis skills. The researcher made a functional analysis of the data from observation of classes taught by participants before the workshop. The analysis focused on the repeated errors made by students, the conditions which may have produced their occurrence and possible alternatives to change these conditions. In some cases, changes were implemented and their effect was successful in students overcoming errors. Participants were seven teachers in a private English language school. Two instruments to evaluate sense of efficacy as a teacher (TES) and sense of responsibility for student achievement (RSA), were applied before and after the second workshop module. Interviews with the teachers were conducted one year after the conclusion of the workshop. The results of the standard instruments showed that teachers presented intermediate or elevated levels of sense of teacher efficacy and responsibility for student achievement at the beginning of the study, most probably due to the established standards and constant supervision of their teaching. Significant change was not observed in the final scores at the end of the workshop. In accordance with the interviews, two participants related improvement in performance for students who presented learning difficulties, as a result of using new teaching strategies based on a functional analysis of student performance. The limitations of the workshop are discussed, particularly in terms of its brief duration and the necessity for a longer period for teaching practice, to maximize the effects on teacher practice. The necessity for evaluation instruments which focus more directly on the skills targeted by the training were also discussed.
Functional Analysis as an Instrument of Inclusion in Foreign Language Teaching
Keywords: Educação especial - inclusão; Dificuldades de aprendizagem; Língua inglesa; Ensino; Professores - formação; Learning difficulties; Inclusion; Functional analysis; Teaching, Sense of teacher efficacy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL